REALITA KEHIDUPAN YANG TERCERMIN LEWAT LATAR DALAM DRAMA RIDERS TO THE SEA KARYA SYNGE - Rahantoknam, Irnando Frits (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This skripsi is entitled â€œRealita Kehidupan yang Tercermin lewat Latar dalam Drama Riders to the Sea Karya Syngeâ€ The objective of this research is to analyze the play in terms of setting using intrinsic and extrinsic approaches. This research is based on Aristotle theory â€œmimetic theoryâ€, and Walek and Warrenâ€™s theory on literature and society. Literature and society are two parts that cannot be separated, both of them have connection with each other. Many of literary works including plays were born from society, so we can see that society has its own part to contribute to literature. In some of literary works we can see the story imitated from the real world. Riders to the Sea is one of the plays which was based on the reality. The playwright John Milington Synge, wrote this play where he visited the Aran islands. In Aran islands he heard a tragedy that happened to one of families there. By that experience, he decided to write play describing the fact that he heard. Based on the analyzing of the setting, this research concludes that there are 5 elements of setting that reflect the social reality of Irish people especially people on Aran Â islands. From the setting of place, setting of time, setting of weather, setting of social condition, and setting of atmosphere. Â  Keywords: Riders to the Sea, setting analysis, intrinsic and extrinsic approach